2021
DOI: 10.3389/fpsyg.2021.759175
|View full text |Cite
|
Sign up to set email alerts
|

Does Embodiment of Verbs Influence Predicate Metaphor Processing in a Second Language? Evidence From Picture Priming

Abstract: Distinct from nominal metaphors, predicate metaphors entail metaphorical abstraction from concrete verbs, which generally involve more action and stronger motor simulation than nouns. It remains unclear whether and how the concrete, embodied aspects of verbs are connected with abstract, disembodied thinking in the brains of L2 learners. Since English predicate metaphors are unfamiliar to Chinese L2 learners, the study of embodiment effect on English predicate metaphor processing may provide new evidence for em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Verbal metaphors are processed via simulation and abstraction, and their meaning is linked with the phrase's meaning (Li et al, 2022 ). Learners often rely on their native language, using the familiar concepts in the native language system to project the corresponding categories in the second language learning (Feng and Zhou, 2021 ; Noor et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Verbal metaphors are processed via simulation and abstraction, and their meaning is linked with the phrase's meaning (Li et al, 2022 ). Learners often rely on their native language, using the familiar concepts in the native language system to project the corresponding categories in the second language learning (Feng and Zhou, 2021 ; Noor et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the abundant research on L1-based embodied mental imagery, there are significantly fewer studies on L2 mental imagery (Feng & Zhou, 2021;Vukovic & Williams, 2014;Wheeler & Stojanovic, 2006). Similar to the patterns of L1 mental imagery, both compatibility (Ahn & Jiang, 2018;Dudschig et al, 2014;Koster et al, 2018;Tomczak & Ewert, 2015) and interference effects (Bergen et al, 2010;Buccino et al, 2017;Vukovic & Williams, 2014;Wheeler & Stojanovic, 2006) have been found in L2 mental imagery research.…”
Section: Mental Imagery In L2 Processingmentioning
confidence: 99%
“…19 , 24 ; cf. also 25 , 26 ] such as culture-specific factors 27 29 , the structure of a specific language and differences in the concreteness and conventionality of stimuli 30 , the proficiency, automaticity and the level of competence of a second language 31 , the age of acquisition 32 and the exposure to L2 environments 33 , 34 . Some studies comparing English and Chinese languages show interesting results in terms of the link between embodiment and L2.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies comparing English and Chinese languages show interesting results in terms of the link between embodiment and L2. Su et al 35 and Feng et al 30 use priming experiments to show that embodied simulation plays a significant role in L2 comprehension and includes both literal and metaphorical sentences. Moreover, its influence appears to be directly proportional to the novelty of the metaphor.…”
Section: Introductionmentioning
confidence: 99%